Art at the service of the revolution in Jesualdo Sosa’s Mi viaje a la URSS (1952) (Anclajes, 2023)
The travel book by Uruguayan educator Jesualdo Sosa, Mi viaje a la URSS (1952) is a significant sample of Soviet cultural programming in the first decade of the Cold War and of the programmed trips to Eastern countries by Latin American intellectuals. Jesualdo, in his intention to show the achievements of Soviet communism, offers a broad review of the most varied aspects of the reality he sees. The purpose of this work is to review the artistic criticisms that the author makes when describing and evaluating different scenic works. Criticisms that show his knowledge of and affiliation to socialist realism.
Keywords: Jesualdo Sosa; Uruguayan literature; Travel book; Socialist realism; URSS